Implications of rituals and authenticity within the spa industry. Issue 2 (4th May 2019) - Poluzzi, Ilaria; Esposito, Simone
ABSTRACT: This manuscript further examines the role of rituals and authenticity, in relation to consumer behaviour, in the spa and wellness sector. In doing so, examples of wellness rituals have been provided and a review of the literature in regards to rituals has been given. Indeed, spas have their specific rituals, performed through the use of products or ingredients, in order to offer customers real experiences, with a total emotional involvement, that creates a multi-sensory journey. These experiences provide memories and positive emotions that, in an experience economy, push customers to look for similar events in the future (Lo et al., 2015; Richins, 2007). However, the factors that contribute to the formation of memorable experiences for guests, in a spa setting, are underexplored concepts and numerous studies call for further explorations (Buxton, 2018; Kucukusta & Guillet, 2014; Lee et al., 2014; Loureiro et al., 2013; Reitsamer, 2015). These would fill the lack of theoretical understanding of ritualisation and authenticity, within the spa services, whose role is influential in creating memorable experiences for spa guests.